What matters to older people with assisted living needs? A phenomenological analysis of the use and non-use of telehealth and telecare - Greenhalgh, P; Wherton, J; Sugarhood, P; Hinder, S; Procter, R; Stones, R (Elsevier, 2013)
Telehealth and telecare research has been dominated by efficacy trials. The field lacks a sophisticated theorisation of [a] what matters to older people with assisted living needs; [b] how illness affects people's capacity to use technologies; and [c] the materiality of assistive technologies. We sought to develop a phenomenologically and socio-materially informed theoretical model of assistive technology use. Forty people aged 60–98 (recruited via NHS, social care and third sector) were visited at home several times in 2011–13. Using ethnographic methods, we built a detailed picture of participants' lives, illness experiences and use (or non-use) of technologies. Data were analysed phenomenologically, drawing on the work of Heidegger, and contextualised using a structuration approach with reference to Bourdieu's notions of habitus and field. We found that participants' needs were diverse and unique. Each had multiple, mutually reinforcing impairments (e.g. tremor and visual loss and stiff hands) that were steadily worsening, culturally framed and bound up with the prospect of decline and death. They managed these conditions subjectively and experientially, appropriating or adapting technologies so as to enhance their capacity to sense and act on their world. Installed assistive technologies met few participants' needs; some devices had been abandoned and a few deliberately disabled. Successful technology arrangements were often characterised by ‘bricolage’ (pragmatic customisation, combining new with legacy devices) by the participant or someone who knew and cared about them. With few exceptions, the current generation of so-called ‘assisted living technologies’ does not assist people to live with illness. To overcome this irony, technology providers need to move beyond the goal of representing technology users informationally (e.g. as biometric data) to providing flexible components from which individuals and their carers can ‘think with things’ to improve the situated, lived experience of multi-morbidity. A radical revision of assistive technology design policy may be needed.